2018
DOI: 10.1002/we.2204
|View full text |Cite
|
Sign up to set email alerts
|

An integral boundary layer engineering model for vortex generators implemented in XFOIL

Abstract: To assess and optimize vortex generators (VGs) for flow separation control, the effect of these devices should be modelled in a cost and time efficient way. Therefore, it is of interest to extend integral boundary layer models to analyse the effect of VGs on airfoil performance. In this work, the turbulent boundary layer formulation is modified using a source term approach. An additional term is added to the shear-lag equation, to account for the increased dissipation due to streamwise vortex action in the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…It is important to highlight that, in XFLRv5, 2D viscous results are imported through XFOIL where 2D Laplace's equation is solved for velocity field. This velocity field is used as an input in XFOIL to solve a boundary layer problem through simultaneous IBL(Interactive Boundary Layer) methodology [26]. XFOIL evaluates total viscous drag in the wake of airfoil using a Squire-Young formula.…”
Section: Proposed Airfoil Analysismentioning
confidence: 99%
“…It is important to highlight that, in XFLRv5, 2D viscous results are imported through XFOIL where 2D Laplace's equation is solved for velocity field. This velocity field is used as an input in XFOIL to solve a boundary layer problem through simultaneous IBL(Interactive Boundary Layer) methodology [26]. XFOIL evaluates total viscous drag in the wake of airfoil using a Squire-Young formula.…”
Section: Proposed Airfoil Analysismentioning
confidence: 99%
“…However, it has the limitation of the simplified nature of the shear term and the calibration for a single VG configuration. De Tavernier et al 32 extended this method for a broader application by proposing a semi-empirical relation between the source term, VG variables and boundary layer properties using a broad range of experimental and high-fidelity numerical data. The source-term integral (I ST ) was discovered to be subject to the most influnence of VG effects.…”
Section: Vortex Generator Modelmentioning
confidence: 99%
“…Daniele et al 31 suggested a sin-exponential increment instead of a step change in 30 , which was shown a good agreement with experimental results and increased numerical stability. De Tavernier 32 further extended Kerho and Kramer's approach 30 by introducing a smooth step function and decay rate to the source strength term to Xfoil 33 . However, all these work based on viscous-inviscid formulation only considers steady flow.…”
mentioning
confidence: 99%
“…Thus, the dimensions of the airfoil can affect the drag force and lift force that occurs. 14 An airfoil is a form of aerodynamics intended to produce a large lift with the smallest possible drag.…”
Section: Natural Sciences Engineering and Technology Journal (Naset J...mentioning
confidence: 99%